2014
DOI: 10.1128/mcb.01710-13
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Network Analysis in Muscle Reveals AP-1 as a Partner of PGC-1α in the Regulation of the Hypoxic Gene Program

Abstract: Skeletal muscle tissue shows an extraordinary cellular plasticity, but the underlying molecular mechanisms are still poorly understood. Here, we use a combination of experimental and computational approaches to unravel the complex transcriptional network of muscle cell plasticity centered on the peroxisome proliferator-activated receptor ␥ coactivator 1␣ (PGC-1␣), a regulatory nexus in endurance training adaptation. By integrating data on genome-wide binding of PGC-1␣ and gene expression upon PGC-1␣ overexpres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 47 publications
3
61
0
Order By: Relevance
“…The high transcript levels of BNP in C2C12 myotubes overexpressing PGC-1α strongly suggest that BNP is indeed regulated by PGC-1α. To further elucidate the epistasis between these two genes, the BNP promoter region was scanned for potential PGC-1α response elements based on previous work on the PGC-1α-controlled transcriptional network in muscle cells12. The activator protein-1 (AP-1) transcription factor protein complex, which binds to Fos-Jun-like motifs, has two predicted binding sites in the genomic region flanking the BNP transcriptional start site (TSS), and is co-activated by PGC-1α12.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high transcript levels of BNP in C2C12 myotubes overexpressing PGC-1α strongly suggest that BNP is indeed regulated by PGC-1α. To further elucidate the epistasis between these two genes, the BNP promoter region was scanned for potential PGC-1α response elements based on previous work on the PGC-1α-controlled transcriptional network in muscle cells12. The activator protein-1 (AP-1) transcription factor protein complex, which binds to Fos-Jun-like motifs, has two predicted binding sites in the genomic region flanking the BNP transcriptional start site (TSS), and is co-activated by PGC-1α12.…”
Section: Resultsmentioning
confidence: 99%
“…To further elucidate the epistasis between these two genes, the BNP promoter region was scanned for potential PGC-1α response elements based on previous work on the PGC-1α-controlled transcriptional network in muscle cells12. The activator protein-1 (AP-1) transcription factor protein complex, which binds to Fos-Jun-like motifs, has two predicted binding sites in the genomic region flanking the BNP transcriptional start site (TSS), and is co-activated by PGC-1α12. Accordingly, siRNA-based silencing of Fos and Jun strongly reduces the ability of PGC-1α to induce BNP expression12.…”
Section: Resultsmentioning
confidence: 99%
“…Several differences in study design may help explain some of the discrepancies between our previous studies and those reported by Baubec et al First, whereas endogenous Mbd3 was examined in ChIP studies performed in Yildirim et al, the bio-tagged Mbd3 in Baubec et al was overexpressed [see Figure S1F from Baubec et al (2013)]. Since overexpression of proteins can promote promiscuous binding as assayed by ChIP (Baresic et al, 2014; Fernandez et al., 2003), it is possible some of the peaks of Mbd3 binding identified by this method are non-physiological. Second, all Mbd3 isoforms were immunoprecipitated in the Yildirim study, rather than the single largest isoform examined in Baubec et al Third, whereas Yildirim et al examined Mbd3 binding to promoter-proximal regions of genes, Baubec et al focused mainly on a subset of LMRs and ICPs.…”
Section: Discussionmentioning
confidence: 87%
“…After the initial presentation of MARA and its application to inferring the core regulatory network of a differentiating human cell line [11], MARA has since been applied to a large number of different mammalian systems [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and extended to model genome-wide chromatin marks in terms of epigenetic motif activities [28]. Remarkably, in all these systems, MARA's predictions of key regulators and their interactions were subsequently confirmed by experimental validation.…”
Section: Motif Activity Response Analysismentioning
confidence: 96%